2015
DOI: 10.1126/science.aab3564
|View full text |Cite
|
Sign up to set email alerts
|

Keeping cool: Enhanced optical reflection and radiative heat dissipation in Saharan silver ants

Abstract: Saharan silver ants, Cataglyphis bombycina, forage under extreme temperature conditions in the African desert. We show that the ants' conspicuous silvery appearance is created by a dense array of triangular hairs with two thermoregulatory effects. They enhance not only the reflectivity of the ant's body surface in the visible and near-infrared range of the spectrum, where solar radiation culminates, but also the emissivity of the ant in the mid-infrared. The latter effect enables the animals to efficiently dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
388
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 602 publications
(401 citation statements)
references
References 25 publications
11
388
0
2
Order By: Relevance
“…Therefore, we cannot exclude the possibility that the high levels of constitutive HSC70 detected in whole-body extracts from C. bombycina stem from the localised accumulation of HSC70 in specific tissues. Moreover, hairs have elevated transmissivity in the mid-infrared range, allowing radiation to bypass the ant's protective coat more readily at those wavelengths (Shi et al, 2015). As a consequence, we may have observed similar mortality rates in the two species because our experimental design did not reproduce the natural balance of incoming solar energy.…”
Section: Heat Hardening and Thermotolerancementioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, we cannot exclude the possibility that the high levels of constitutive HSC70 detected in whole-body extracts from C. bombycina stem from the localised accumulation of HSC70 in specific tissues. Moreover, hairs have elevated transmissivity in the mid-infrared range, allowing radiation to bypass the ant's protective coat more readily at those wavelengths (Shi et al, 2015). As a consequence, we may have observed similar mortality rates in the two species because our experimental design did not reproduce the natural balance of incoming solar energy.…”
Section: Heat Hardening and Thermotolerancementioning
confidence: 74%
“…Indeed, recent studies have shown that the dorsal side of C. bombycina workers (but not of C. mauritanica workers) is covered by a unique array of prism-shaped hairs that reflect incident sunlight and are responsible for the species' silver colour ( Fig. 1) (Shi et al, 2015;Willot et al, 2016). The hairs are thermally protective in the visible and near-infrared range of the electromagnetic spectrum, reducing the absorption of sunlight energy and leading to lower internal body temperatures in workers.…”
Section: Heat Hardening and Thermotolerancementioning
confidence: 99%
“…Yu and co-workers recently reported the thermoregulatory strategies that enable Saharan silver ants to forage in the midday sun on the desert surface where temperatures can reach 70 • C (which is not survivable by their primary predators). It was found that a monolayer of densely packed hairs with peculiar triangular cross-sections, in some sense a biological "metasurface", enhances not only the ant body's reflectivity in the visible and near-infrared, where solar radiation culminates, but also its emissivity in the midinfrared [248]. The combined effect enables the ants to minimize absorption from solar radiation, and to efficiently dissipate heat back to the surroundings via blackbody radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Desert silver ants have relatively high solar reflecting backs so they can find food in the fierce daytime heat to avoid night predators [104]. A most important example is leaves.…”
Section: Mimicking Natural Nanostructuresmentioning
confidence: 99%